AdvisOnt: Семантизація сервісів агродорадництва для валідації результатів неформального та інформального навчання. II - Строкань, О.В.; Прийма, С.М.; Рогушина, Ю.В.; Гладун, А.Я.; Лубко, Д.В.; Мозговенко, А.А. (Control systems & computers, 2021)
Розглянуто специфіку діяльності дорадчих систем, їхні цілі та призначення. Обґрунтовано доцільність використання семантичних технологій для документації та валідації результатів неформального та інформального навчання, характерних для сільського господарства. Запропонована система AdvisOnt (Advisory Ontology System), яка базується на онтологічному поданні знань про компетенції, вакансії, навчальні курси та профілі користувачів, призначається для розробки рекомендацій щодо працевлаштування або подальшого набуття необхідних компетенцій. We propose advisory system AdvisOnt that analyses the outcomes of non-formal and informal learning and ensures their validation for more efficient matching of information about potential employees, employers and agricultural educational resources. AdvisOnt is based on ontological representation of this knowledge formalized by competencies, vacancies, training courses, user profiles etc. System is aimed to generate recommendations for employment or further learning of necessary competencies by matching of these objects. External knowledge bases are used for semantic formalization of vacancies and resumes for their more pertinent matching with the help of agricultural domain knowledge and competence classifications. AdvisOnt users receive recommendations on employment and about training courses that provide advisable competencies.